A new method for detection of unbalance voltage supply in three phase induction motor - Sheikh, M.A. (Penerbit UTM Press, 2016)
Induction motors are associated with various techno-economic advantages; therefore these are widely used in residential, commercial and industrial systems. Cost effective and reliable process of condition monitoring of induction motor is very important. It is found that unbalance voltage supply is one of the major factors that produce uneven heating due to reverse current and leads to inter-turn short circuit. The issue regarding unbalanced voltage supply has attracted the attention of researcher and engineers in recent past. In this paper, a new effective non-invasive (online) method is proposed that only use rotor harmonic current signature for the detection of unbalance voltage supply instead of main line current signature. This is a sensor-less and online approach that accomplishes the reliable and accurate analysis of the induction motors. Moreover, it allows a continuous real time tracking without disturbing the normal operation and guarantees the overall production process. Additionally, this method recognizes the unbalance and estimate the severity of the unbalance in the voltage source. The effects of unbalance voltage supply are investigated through experiments. In order to perform the analysis and detect the asymmetry due to unbalance voltage, an experimental set up is designed that can accurately repeat the measurements. In the proposed work, unbalance voltage supply is diagnosed through experimental hardware setup. To validate the propose methods an experiment is performed that confirm that motor operating under unbalance voltage supply give a significant rise in the rotor harmonic while under balance voltage supply there is so such a rise in the rotor harmonic. Â© 2016 Penerbit UTM Press. All rights reserved.